Orthodontic movement after periodontal regeneration of class II furcation: a pilot study in dogs - Vanessa Camila da Silva (journal of clinical periodontology, 2006)
Purpose: The effect of orthodontic movement on the periodontal tissues of maxillary second pre-molars, after regenerative treatment for class II furcations, was evaluated in four mongrel dogs. Material and Methods: Class II furcation lesions were created. After 75 days they were treated with bovine bone mineral matrix and guided tissue regeneration with absorbable membrane. After 2 months of daily plaque control, each of the dog’s furcation pre-molars was randomly assigned to a test or control group. Orthodontic appliances were placed on both sides of the maxilla using third pre-molars and canines as anchorages. In the test group, bodily orthodontic movement of the second premolars was performed in the mesial direction for 3 months while control pre-molars remained unmoved. The dogs were sacrificed for histometric and histologic analyses. Results: There were no statistically significant differences between the two groups in total bone and biomaterial areas or linear extension of periodontal regeneration on the radicular surfaces. In the test group, however, there was a tendency to a greater quantity of bone and a lesser quantity of biomaterial. Conclusion: The orthodontic movement was not pre-judicial to the results obtained with the regenerative periodontal treatment.